Akuntansi Dana Desa (Studi Wacana Pada Desa Nupabomba Dan Wani II Kecamatan Tanantovea Kabupaten Donggala) - Fadli, Mohammad (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2018)
This research aimed to identify, analize, and synthesize the administration and reporting process of village funds. It used the qualitative method with discourse aprroachment.The result of this research showed that the administration process are still constrained by the limited number of human resources and lack of understanding about regulation. Reporting mechanisms undertaken by the village government seem